PENGARUH KEPALA DESA DALAM MENINGKATKAN KINERJA PERANGKAT DESA DI DESA MONTA BARU KECAMATAN LAMBU KABUPATEN BIMA - Septi Hikmatun; Nirwana Nirwana (Universitas Mbojo Bima, 2022)
The effectiveness of communication is assessed from the performance of human resources in the organization. An important element in improving performance in an organization is the availability of quality human resources, productivity, has a high work ethic, and is able to make an optimal contribution. The purpose of this study was to determine the role of the village head, communication skills, communication styles, reciprocal relationships between leaders and subordinates. This type of descriptive quantitative research, while the number of samples is 30 with a total population of 2,630. by developing an instrument in the form of a questionnaire given to each respondent who visited the Monta Baru Village Office, Lambu District, Bima Regency. Then the data analysis technique used is to analyze the data based on the respondent's answer to the questionnaire. As for the results of the study, it can be explained that as many as 78.80% of respondents said it was very good, then 8% good, then the respondents answered quite well 3.15% and the respondents who answered were not good at 0%. Based on the data obtained, the intensity of communication built by the village head was very good and needed to be maintained as a form of communication reconstruction effort. The conclusion is that based on the data it can be said that the respondents who answered 79.03% were very good, this shows that the influence of the village head's communication in improving the performance of the apparatus was very good.